Examining South Korean university students’ interactions with international students / Andrea Rakushin Lee and Daniel R. Bailey - Lee, Andrea Rakushin; Bailey, Daniel R. (Universiti Teknologi MARA, 2020)
This mixed method case study examines South Korean university students’ social and academic interactions with international students. Data included a closed-ended survey, an open-ended survey, and a focus group. The participants comprised university students studying at a mid-sized university in central South Korea. Results indicate that students generally feel indifferent about interacting with international students and stated that communication barriers and lack of contributions by international students on assignments lead to less interaction. Moreover, quantitative data reveals a lack of interest in interacting with international students. To improve interaction, students recommended providing more opportunities to communicate in the classroom and taking intercultural communication classes to increase understanding of diverse cultures. Additionally, students recommended sharing dorm rooms with international students, creating more social activities for interaction, and developing language, culture, and mentoring programs. Various practical and theoretical implications are discussed to help improve social and academic interactions and increase intercultural communication on campus.